(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article will consider the current state of attracting investments in the tourism sector of Uzbekistan and the trends affecting its development. Relying on various sources, including government reports, Field Analysis and expert opinion, the study offers a comprehensive analysis of the dynamics and trends in investment in the tourism industry.